2015
DOI: 10.1080/14330237.2015.1078089
|View full text |Cite
|
Sign up to set email alerts
|

Influences on life aspirations among adolescents in a low-income community in Cape Town, South Africa

Abstract: The aim of this study was to determine the influences on adolescents' aspirations from a low-income community in Cape Town . A sequential mixed method exploratory design was used following two distinct phases . The qualitative phase comprised focus group interviews with 118 grade 12 learners attending a school in a low-income community (age range: 16-19 years) and focused on identifying factors influencing life aspirations . The quantitative phase with 191 adolescents (males = 54 .45 %, females = 45 .55 %); ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…With regard to the current study, Hendricks et al (2015) found social support to significantly predict adolescents' aspirations; while a lack of social support was specifically identified as a factor that hindered adolescents' aspirations. In an important contribution to the literature, Jacobson (1987) advances a meaning-centred approach to understanding the role of social support.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…With regard to the current study, Hendricks et al (2015) found social support to significantly predict adolescents' aspirations; while a lack of social support was specifically identified as a factor that hindered adolescents' aspirations. In an important contribution to the literature, Jacobson (1987) advances a meaning-centred approach to understanding the role of social support.…”
Section: Introductionmentioning
confidence: 57%
“…Research involving social support often considers the mediating role that it plays within certain relations—such as the relation between the quality of friendship and psychological well‐being, gratitude and school well‐being and loneliness and life satisfaction (see Bakalim & Taşdelen‐Karçkay, 2016; Sun, Jiang, Chu, & Qian, 2014; Yildiz & Karadas, 2017). With regard to the current study, Hendricks et al (2015) found social support to significantly predict adolescents’ aspirations; while a lack of social support was specifically identified as a factor that hindered adolescents’ aspirations. In an important contribution to the literature, Jacobson (1987) advances a meaning‐centred approach to understanding the role of social support.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations